2020
DOI: 10.1177/0309364620969226
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb prosthetic interfaces

Abstract: The human–prosthesis interface is one of the most complicated challenges facing the field of prosthetics, despite substantive investments in research and development by researchers and clinicians around the world. The journal of the International Society for Prosthetics and Orthotics, Prosthetics and Orthotics International, has contributed substantively to the growing body of knowledge on this topic. In celebrating the 50th anniversary of the International Society for Prosthetics and Orthotics, this narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 190 publications
0
56
0
Order By: Relevance
“…To address this issue, adjustable sockets have been developed in the field with both smart and manually controlled systems [9,14,22,[25][26][27]. Pressure-whether qualitative or quantitative-is often the prescribed scale against which adjustable socket volumes are altered.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To address this issue, adjustable sockets have been developed in the field with both smart and manually controlled systems [9,14,22,[25][26][27]. Pressure-whether qualitative or quantitative-is often the prescribed scale against which adjustable socket volumes are altered.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, rehabilitation is especially difficult for transfemoral amputees, and research indicates that a high amputation level is associated with both prosthetic non-use and a decreased probability of remaining ambulatory [ 2 , 3 ]. Socket fit has been cited as one of the main factors affecting gait re-education, rehabilitation, and quality of life for amputees from the viewpoint of both amputees and clinicians [ 4 , 5 , 6 , 7 , 8 , 9 ]. Poor socket fit is the cause of at least one gait deviation, in people with lower limb amputation, which could be linked to premature long-term musculoskeletal degenerations [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five trials were recorded, during which at least one gait cycle could be identified using the force plate data. Focusing on a full gait cycle for each leg, based on both kinematics and kinetics measurements and the identification of the heel strike and toe-off events, the mean value of the following parameters was calculated: 21, 22 1) Walking speed (m/s), 2) Cadence (steps/min), 3) Step width (m), 4) Stride length (m), 5) Double support (%), 6) Hip extension (degrees). 23 For a subset of the above mentioned gait analysis parameters, the DoA was also calculated: Hip angles on the sagittal plane of both legs were exported in MATLAB.…”
Section: Gait Analysismentioning
confidence: 99%